Investigating Influencing Factors of Shoreline Changes in Bantul's Tourist Coastal Areas Using GIS and Satellite Data - Buddin Al Hakim; Destianingrum Prabawardani; Tjahjono Prijambodo; Nugraheni Setyaningrum; Andung Bayu Sekaranom; Eki Aurora Shakyra (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
The littoral zone is the most vulnerable area to the impacts of climate change and human activities. Current weather anomalies and the development of human activities in coastal areas are on the rise. Remote sensing and geographic information system approaches have been widely used to monitor shoreline changes using easily accessible satellite imagery. This study aims to identify the dominant factors driving littoral change at Bantul Beach and assess the relationship between tourism activity and coastal abrasion. This study uses the Geographic Information System (GIS) analysis method using Landsat-8 satellite imagery from 2013 to 2023. In monitoring shoreline changes, NDWI and DSAS analyses were conducted to identify factors influencing coastal changes. A study was also conducted to examine the parameters of the coastal profile, wind, waves, tides, and human activities. Based on 10 years of image data, the study location has generally experienced high abrasion, with an average EPR value of -1.51 m/year, an average SCE value of 47 meters, and a dominant negative NSM value. The most influential factors are the slope of the shoreline and waves, especially during high waves or storms. The increase in the number of tourists in Bantul Yogyakarta tourism spots is not linearly correlated to the occurrence of abrasion. There needs to be coastal protection and mitigation that prioritizes the dominant factors causing abrasion, utilizing a soft engineering approach and local wisdom.Keywords: Shoreline changes, Tourist Coastal Areas, DSAS, Landsat-8, Bantul Yogyakarta